Animal explorer: a walk in the jungle / Nurul Irdina Shahrizam and Siti Fatimah Mohd Rum - Shahrizam, Nurul Irdina; Mohd Rum, Siti Fatimah (College of Computing, Informatics, and Mathematics, 2024)
The Animal Explorer: A Walk in the Jungle, an interactive multimedia-based smartphone application tailored for elementary school students in standard 4,5 and 6, seeks to enhance science learning experiences. Specifically designed for portable and hand- held touch-controlled gadgets, the application addresses the challenges encountered by elementary students in comprehending the intricate components of the Classification of Animals. The project's primary focus is to assist students in successfully learning about classified animals in the vertebrates and invertebrates group, aiming to alleviate the difficulties associated with understanding this complex topic. The methodology used in this project is the ADDIE methodology. ADDIE methodology, divided into 5, which is analysis, design, development, implementation, and evaluation phases, ensures an efficient and planned development process for the interactive learning program. Based on the System Usability Scale (SUS) questionnaire in the survey, the application that has been developed is confirmed to be excellent with a 95.10% percentage of participants agreeing that the application is enjoyable, efficient, interactive, and user-friendly. In conclusion, the integration of the ADDIE method with interactive elements results in the creation of an effective and engaging educational tool, offering students a multimedia-rich learning experience that enhances overall success in science education at the elementary school level.